A Study on Talent Management Practices for Succession Planning with Reference to Selected IT/ ITES Organizations in Coimbatore, Tamil Nadu - Natarajan, Sundarapandiyan; Babu, S. (Prabandhan: Indian Journal of Management, 2018)
The main objective of this study was to find out the current talent management practices on succession planning of IT/ITES organizations in Coimbatore, Tamil Nadu. A descriptive study was carried out, and original and factual data from the employees of IT/ITES organizations located in Coimbatore were collected through closed ended and open ended question types using a 5 point Likert scale questionnaire. The data were collected on various dimensions of talent management practices including hiring the best talents, training and development of employees, compensation and rewards to the performers, and talent retention and succession planning. The study was based on primary data collected from employees of 10 IT and ITES organizations, most of which are global players, with the help of a pre-tested and structured questionnaire. Out of the 414 responses, 363 responses were screened out for error free data analysis. The collected data were analyzed using statistical tools to bring out talent management practices and the opinions of employees on the important factors to be considered to maintain talent retention and proper succession planning. It was found that there was a strong correlation between talent management practices (compensation plan, performance appraisal, learning and development, and rewards and recognition) and talent retention & succession planning among the IT/ITES organizations in Coimbatore, Tamil Nadu.